2004
DOI: 10.1353/ecs.2004.0064
|View full text |Cite
|
Sign up to set email alerts
|

Raising Hair

Abstract: In the eighteenth century hair was recognized as possessing fundamental communicative and cultural power. At once a natural extension of the body and a craftable sign, hair served to mark as well as blur boundaries between, for example, nature and culture, man and woman, human and animal. This essay focuses on the discursive and performative ways in which hair linked notions of human variety to gendered, ethnic, and racial differences. It also serves to introduce the eleven interdisciplinary essays in this vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…118 European hair was characterized as long and blond as a result of the moderate climate, contrasting with the short, curly hair of Africans, or the black, straight hair of Americans, both of whom inhabited hot climates. 119 Beards, as Angela Rosenthal suggests, were perhaps even more meaningful than hair, as they linked both gender and ethnicity. 120 By 1700, the quality, length and colour of beards were important elements in discussions of non-European bodies, becoming central components in establishing ranks or 'sorts' of homo sapiens.…”
Section: Beards Race and Corporeal Valuementioning
confidence: 99%
“…118 European hair was characterized as long and blond as a result of the moderate climate, contrasting with the short, curly hair of Africans, or the black, straight hair of Americans, both of whom inhabited hot climates. 119 Beards, as Angela Rosenthal suggests, were perhaps even more meaningful than hair, as they linked both gender and ethnicity. 120 By 1700, the quality, length and colour of beards were important elements in discussions of non-European bodies, becoming central components in establishing ranks or 'sorts' of homo sapiens.…”
Section: Beards Race and Corporeal Valuementioning
confidence: 99%
“…Angela Rosenthal highlights the use of the beard as a racial characteristic in the depiction of Jewish men in satirical prints. 41 It is no coincidence that Clubbe's Letter of Free Advice to a Young Clergyman also advised the subject 'not to come into that Jewish fashion of wearing a skirting of beard around the face'. 42 A third possibility may be the intrusion of aesthetics into bodily ideals.…”
Section: Facial Hair and Masculinity In The Eighteenth Centurymentioning
confidence: 99%
“…Wearing a beard became less popular in the eighteenth century. 134 Changes to the production and advertising of steel razors made the new clean shaven ideal more easily obtainable. 135 Despite the increasing preference to remove facial hair that obscured the 'true' face, the meaning attributed to beards was still important in this era of new world contact though as Europeans defined their own sense of moral development, in part, by contrasting themselves with the largely beardless indigenous population of America.…”
mentioning
confidence: 99%
“…137 Some argued that the thin, sparse hair of Indigenous Americans, and Asians, aligned them with the less than manly eunuchs and castrati. 138 The question of whether the men of these nations were naturally hairless or artificially plucked their hair from their bodies was an important one because it was taken as an indicator of their ability to adapt to European ways of life. 139 Natural hairlessness, according to some commentators, revealed that such men were 'stunted' and so would not adapt to new modes of civility.…”
mentioning
confidence: 99%